2016
DOI: 10.1038/oncsis.2016.75
|View full text |Cite
|
Sign up to set email alerts
|

Linking genomic reorganization to tumor initiation via the giant cell cycle

Abstract: To investigate the mechanisms underlying our recent paradoxical finding that mitotically incapacitated and genomically unstable polyploid giant cancer cells (PGCCs) are capable of tumor initiation, we labeled ovarian cancer cells with α-tubulin fused to green fluorescent protein, histone-2B fused to red fluorescent protein and FUCCI (fluorescent ubiquitination cell cycle indicator), and tracked the spatial and time-dependent change in spindle and chromosomal dynamics of PGCCs using live-cell fluorescence time-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
151
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(159 citation statements)
references
References 47 publications
5
151
0
3
Order By: Relevance
“…In any case, converging evidences indicated that MNGCs ultimately contribute to the generation of progeny with stem cell-like properties and may have a fundamental role in cancer recurrences and chemoresistance [22,38]. This phenotype was also observed in several studies performed on ovarian cancer models [44][45][46][47][48]. Future studies are, however, necessary to properly clarify the molecular mechanisms underlying the formation of MNGCs and how TP53 MUT contribute to this phenotype.…”
Section: Discussionmentioning
confidence: 73%
“…In any case, converging evidences indicated that MNGCs ultimately contribute to the generation of progeny with stem cell-like properties and may have a fundamental role in cancer recurrences and chemoresistance [22,38]. This phenotype was also observed in several studies performed on ovarian cancer models [44][45][46][47][48]. Future studies are, however, necessary to properly clarify the molecular mechanisms underlying the formation of MNGCs and how TP53 MUT contribute to this phenotype.…”
Section: Discussionmentioning
confidence: 73%
“…There is a small body of literature specifically related to PGCCs (74 PubMed‐listed entries with query: [PGCCs] vs 3,857,567 with query [cancer]; accessed 10 May 2019; Figure ), but this literature, taken holistically, makes a compelling case for defining them as the essential keystone cancer species and actuators of tumorigenesis, therapeutic resistance, and recurrence in metastatic disease. Keystone species are relatively few in number, but have a significant impact on the health and composition of the ecosystem.…”
mentioning
confidence: 99%
“…This model readily accounts for the well-established notion that interruption of the menstrual cycle via either pregnancy or oral contraceptive use has profound protective effects against high-grade serous extra-uterine Müllerian and breast carcinomas not only in the general population, 28,29 but also in BRCA1 mutation carriers. [31][32][33] The molecular events leading to cytokinesis failure and polyploidy, which are discussed here in the context of their role in predisposition to malignant transformation in BRCA1 mutation carriers, most likely continue to operate after malignant transformation has taken place, when they might contribute to the generation of polyploid giant cancer cells, recently shown in Jinsong Liu's laboratory 34,35 to express normal and cancer stem cell markers and to have the ability to increase their viability by reducing their DNA content via asymmetric divisions, budding or bursting. This group suggested that these events, which are related to an early embryological mechanism common in the blastomere stage of preimplantation embryos, may represent important mechanisms for generating cancer stemlike cells and may also contribute to tumor heterogeneity.…”
Section: Discussionmentioning
confidence: 97%